Generation and Control of Basic Geometric Trajectories for a Robot Manipulator Using CompactRIO® (2017)
The utility of a robot manipulator focuses on the ability to locate its end effector in a position with a determined orientation following a specified trajectory. For this, algorithms were used in order to generate and control the movements joints of robot in a synchronized way. The high-level languages to program robots are based on three types of movement: joint interpolation (MOVEJ), linear interpolation (MOVES), and circular arcs (MOVEC), which are used to develop any type of task. In this work, these three movements are implemented in the industrial controller CompactRIO, as part of the reconditioning process of a robot manipulator of five degrees of freedom (5 DOF) whose controller was obsolete. As a result, it will have an interface in LabVIEW where you can view and modify the basic parameters implemented in the industrial controller. In addition, the results of the validation tests of the joint positions and the end effector of the manipulator will be found.